2012
DOI: 10.1002/eji.201142004
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D isoforms are dispensable for integrin‐mediated lymphocyte adhesion and homing to lymphoid tissues

Abstract: Leukocyte function-associated antigen-1 (LFA-1) and very late antigen-4 (VLA-4) integrins are essential for lymphocyte adhesion, trafficking and effector functions. Protein kinase D (PKD) has previously been implicated in lymphocyte integrin regulation through regulation of Rap1 activity. However, the true role of PKD in integrin regulation in primary lymphocytes has not previously been investigated. The major PKD isoform in lymphocytes is PKD2. Here we employed PKD2-deficient mice, a specific PKD kinase inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 55 publications
0
9
2
Order By: Relevance
“…PKC/protein kinase D (PKD) signaling are downstream of phospholipase C in cells, and PKC isoforms have recently been implicated in neutrophil adhesion strengthening under conditions of shear flow (17). However, effector T cell adhesion to ICAM-1 under shear flow conditions is independent of PKC (this report), and we have previously reported that it is also independent of PKD (9). In contrast, we now show the process to be dependent on calcium/calmodulin signaling downstream of the active integrin.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…PKC/protein kinase D (PKD) signaling are downstream of phospholipase C in cells, and PKC isoforms have recently been implicated in neutrophil adhesion strengthening under conditions of shear flow (17). However, effector T cell adhesion to ICAM-1 under shear flow conditions is independent of PKC (this report), and we have previously reported that it is also independent of PKD (9). In contrast, we now show the process to be dependent on calcium/calmodulin signaling downstream of the active integrin.…”
Section: Discussioncontrasting
confidence: 37%
“…Adhesion Assay under Shear Flow-The assay was performed essentially as described (8,9). Ibidi -slides VI 0.4 were coated with 6 g/ml (unless otherwise stated) ICAM-1 overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where appropriate, cells were stimulated with 200 nM PdBu (Sigma-Aldrich), 10 mg/ml anti-BCR (R&D Systems), 10 mg/ml anti-CD3 (R&D Systems), 0.2 mg/ml LPS (Sigma-Aldrich), or 5 mM MgCl 2 + 1 mM EGTA immediately before being added to the plate. Cells were allowed to adhere for 30 min at 37˚C before gentle washing and detection, as described (12).…”
Section: Static Adhesion Assaysmentioning
confidence: 99%
“…Where indicated, cells were stimulated with 200 nM PdBu (Sigma-Aldrich) or 10 mg/mL anti-CD3 (clone 2C11; R&D Systems) immediately before addition to the plate for 30 minutes at 37°C, before gentle washing and detection as previously described. 19 Adhesion under shear flow Ibidi VI 0.4 m-slides were coated with 6 mg/mL ICAM-1 overnight at 4°C. Alternatively, mouse endothelial cells (bEnd.3 cells) were grown on plates and stimulated for 24 hours with 10 ng/mL TNFa.…”
Section: Static Adhesion Assaysmentioning
confidence: 99%